DNA‐Encoded Dynamic Combinatorial Chemical Libraries1. (26th May 2015) - Reddavide, Francesco V.; Lin, Weilin; Lehnert, Sarah; Zhang, Yixin
Abstract Dynamic combinatorial chemistry (DCC) explores the thermodynamic equilibrium of reversible reactions. Its application in the discovery of protein binders is largely limited by difficulties in the analysis of complex reaction mixtures. DNA‐encoded chemical library (DECL) technology allows the selection of binders from a mixture of up to billions of different compounds; however, experimental results often show low a signal‐to‐noise ratio and poor correlation between enrichment factor and binding affinity. Herein we describe the design and application of DNA‐encoded dynamic combinatorial chemical libraries (EDCCLs). Our experiments have shown that the EDCCL approach can be used not only to convert monovalent binders into high‐affinity bivalent binders, but also to cause remarkably enhanced enrichment of potent bivalent binders by driving their in situ synthesis. We also demonstrate the application of EDCCLs in DNA‐templated chemical reactions.